PENERAPAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING (CRT) PADA PEMBELAJARAN IPAS UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS 4B SDN PANDANWANGI 3 - Phalupy, Nindya Dyas; M. Anas Thohir; Siti Amzah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Quality education is education that is able to meet the various needs and characteristics of students. Education must be designed to produce practical skills that can be used directly in solving real-life problems. IPAS or Natural and Social Sciences is one of the integrated subjects created to hone students' critical and rational thinking skills (Hendra et al., 2024). The independent curriculum presents significant changes by integrating science and social studies subjects into one unit, namely IPAS. This is done to create a more comprehensive and contextual student learning experience. In cycle I, although there has been an increase compared to pre-cycle conditions, student learning outcomes have still not fully achieved the expected completion target.